Hubungan Motivasi dengan Hasil Belajar IPA Siswa Selama Pembelajaran Tatap Muka Terbatas - Meri Meri; Enywaty Enawaty; Masriani Masriani; Rini Muharini; Maria Ulfah (Hydrogen: Jurnal Kependidikan Kimia, 2022)
Limited face-to-face learning (PTMT) has been carried out but the implementation of the learning process which lasts 30 minutes for one meeting in learning makes the teacher only convey essential material. Face-to-face learning is more effective than online learning. Motivation is one of the important factors in the success of a learning. This study aims (1) to determine the science learning motivation of class VIII students of SMPN 4 Pontianak even semester 2021-2022 during PTMT, (2) to determine the relationship between learning motivation and science learning outcomes for class VIII students at SMPN 4 Pontianak even semester 2021-2022 during PTMT. The research subjects were students of class VIII SMPN 4 Pontianak. The research method is descriptive with a quantitative approach. Science learning outcomes are obtained from the average daily science test scores of students. This research is a descriptive research with a quantitative approach. Data collection techniques use direct, indirect, and documentation communication. Descriptive statistics were used as a data analysis technique. The results showed that the average learning motivation was 70.81% while the percentage of learning outcomes was 81.4%. Both motivation and learning outcomes are included in the high category. The results of the  Spearman's Rho test between science learning motivation and science learning outcomes obtained (r = 0.019) < ( r = 0.05) which means that there is a relationship between motivation and science learning outcomes for SMPN 4 Pontianak students, namely the higher the motivation, the higher the student learning outcomes. the higher it is. The results of this study can be concluded that the science learning motivation of SMPN 4 Pontianak students in the even semester of 2021-2022 is high with a percentage of 70.81%. There is a significant and positive relationship between learning motivation and learning outcomes for science students of class VIII SMPN 4 Pontianak even semester 2021-2022 during PTMT.